Exiliados en la "edad de oro". Redes y políticas culturales del exilio gallego en el campo editorial argentino de la década del cuarenta: publicaciones periódicas, colecciones y editoriales - Gerhardt, Federico (2015)
The article analyzes the editorial projects promoted during the 40s by a group of Galician exiles in Buenos Aires a result of the Spanish Civil War, in the so called "golden age" of Argentina's publishing industry. The visible figures of the group are Rafael Dieste, Luis Seoane, Arturo Cuadrado and Lorenzo Varela. The investigation focuses on the one hand, in the catalogs of the publishing houses and collections established or directed by the Galician exiles in the period: Biblioteca Billiken, Colección Oro, Hórreo, Dorna, Buen Aire and Nova. On the other hand, examines the literary magazines published simultaneously by the same exiles: De Mar a Mar, Correo Literario and Cabalgata.